2002
DOI: 10.1097/00006123-200202000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Angiography of Intracranial Aneurysms Treated with Endovascular Placement of Guglielmi Detachable Coils

Abstract: Late angiographic follow-up monitoring of aneurysms that have been treated with GDCs demonstrates the durability of the treatment. Aneurysms with large residual neck remnants were subjected to further treatment, whereas aneurysms with small residual neck remnants remain under observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 22 publications
1
75
0
3
Order By: Relevance
“…There is the wide variation in reported anatomic results after coiling, which may be attributable to differences in aneurysm characteristics, coil packing density, imaging modalities, or analytic methods [22,23]. Although angiographic occlusion status is, to some extent, subjective and complacent, recently published reports have shown that the independent evaluations were complete occlusion in 44.0-47.4%, neck remnant in 25.0-41.9%, and aneurysm remnant in 10.7-31.0% of aneurysms [24,25].…”
Section: Anatomic Results Of Coiled Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is the wide variation in reported anatomic results after coiling, which may be attributable to differences in aneurysm characteristics, coil packing density, imaging modalities, or analytic methods [22,23]. Although angiographic occlusion status is, to some extent, subjective and complacent, recently published reports have shown that the independent evaluations were complete occlusion in 44.0-47.4%, neck remnant in 25.0-41.9%, and aneurysm remnant in 10.7-31.0% of aneurysms [24,25].…”
Section: Anatomic Results Of Coiled Aneurysmsmentioning
confidence: 99%
“…As most aneurysm recanalizations, rebleeding, or retreatment are reported to occur within 1 year after coiling [9,[18][19][20][21][22], this study examined predictors for residual aneurysms at 1-year follow-up and retreatment within 1 year, demonstrating dome size of ≥7.5 mm, pre-treatment aneurysm re-rupture, non-small size/small neck aneurysm (dome size, ≥10 mm or neck size, ≥4 mm), and residual aneurysms on immediate post-coiling DSA as significant factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors claim that recurrences occur early, rarely if ever after 6 months [22,49]. In the ISAT, the mean time to late retreatment was 5.7 months.…”
Section: Recurrences and Retreatmentmentioning
confidence: 99%
“…Depending on the technique applied and on anatomy, the rate of recanalization or partial recanalization is considerable, ranging between 0 and 35% [28,29,[40][41][42]. Treatment of recurrences after coil compaction (Figure 9) with repeated coiling appears, however, to be less problematic and less risky [43] than the initial coil treatment, since the initial coil partially protects the aneurysmal dome.…”
Section: Detachable Coilsmentioning
confidence: 99%